APLIKASI SISTEM PEMESANAN DAN PENYEWAAN SARANA OLAHRAGA (SAROLA) MENGGUNAKAN ANDROID - Dedi Apriadi; Indra Maulana Yusup Kusumah; Heldan Muhammad Haidar (LPPM STMIK BANDUNG, 2022)
The Sports Facility Application is an information system for ordering and renting long-distance sports facilities based on the Android operating system using an internet connection. Booking and rental sports facilities are generally still done conventionally by most entrepreneurs in the sports facility booking and rental business, which makes it difficult for customers to get information from the rental place in real time. BCNY HOUSE which becomes the subject of the research is one of companies that still uses conventional rental methods. The marketplace concept applied to the Sports Facility Application is expected to be a solution to the problems that exist in conventional sports facility booking and rental methods. This system aims to provide convenience to customers and owners of sports facilities, which will become a bridge between them. This application offers various facilities to get real time information in booking and renting sports facilities. The research was conducted using qualitative methodology, with data collection research methods carried out at BCNY HOUSE and software development methods using the waterfall method (Classic Life Cycle). The model described by Roger S. Pressman (1992: 24) has general steps including analysis, design, implementation, testing, deployment and maintenance. The implementation of the Sports Facilities Application is made with facilities including sports facilities management, field data management, facility information management, booking management, profile management, facility schedule management and report information management for admin. Keywords : Application, Booking and Renting, Sport Facility, Sarola, Waterfall, UML.